Is There Life After DEBI? Examining Health Behavior Maintenance in the Diffusion of Effective Behavioral Interventions Initiative. Issue 3 (6th February 2014) - Feldman, Matthew B.; Silapaswan, Andrew; Schaefer, Nathan; Schermele, Daniel
Abstract: The evidence‐based interventions that are identified, packaged, and disseminated by the Division of HIV/AIDS Prevention at the Centers for Disease Control and Prevention as part of the Diffusion of Effective Behavioral Interventions (DEBI) initiative—commonly referred to the "DEBIs"—currently represent a primary source of HIV prevention interventions for community‐based providers. To date, little attention has focused on whether the intended outcomes of the DEBIs, i.e., reductions in HIV‐related risk behaviors, are maintained over time. This review summarized evidence for the sustainability of the effects of the DEBIs on HIV sexual risk behavior and intravenous drug use from studies of original and adapted DEBIs. Evidence of intervention decay or a lack of any intervention effect was identified in several original and adapted versions of the DEBIs included in this review. Recommendations include modifications to current criteria for inclusion in the DEBI portfolio, in addition to the development of remediation strategies to address intervention decay. Further, theoretical models that specify the processes that underlie the maintenance of health behaviors over time should be used in developing HIV prevention interventions.